The Effect of Pregnant Women's Class on Primigravida Mother's Anxiety in Pegajahan Puskesmas, Pegajahan District, Serdang Bedagai Regency in 2022 - Isyos Sari Sembiring; Halimatun Sakdiyah; Pristiwanti; Susanti; Arifah; Surya Dani (Institute of Computer Science (IOCS), 2022)
High population growth causes a population explosion These physical changes cause psychological and emotional conditions to become unstable so that it fosters constant worries until the end of her pregnancy. According to Mansur (2018), almost 80% of pregnant women experience disappointment, refusal, anxiety, anxiety, depression and moodiness and the incidence of mental disorders by 15% occurs in primigravida mothers in the first trimester. Worries and anxiety in pregnant women if not treated seriously will have a bad impact and influence. Poor health and mental health during pregnancy can have a lasting impact on the quality of life for the mother and the cognitive development of her child (Arini et al, 2018). Emotional disturbances in pregnant women will affect the behavior of maintaining health during pregnancy, such as being lazy to eat, lazy to take a bath, sleep disturbances and fatigue (Andriana, 2017). Aprilia's research (2018) also proves that the effects of stress can increase the risk of miscarriage, preeclampsia, impaired fetal growth, premature birth and postnatal developmental delays and reduce the mother's immune response.